FRAUD DIAMOND DETERMINANTS OF POTENTIAL FINANCIAL REPORTING FRAUD - Lisa, Oyong; Farhan, Djuni; Dahlan, Ahmad; Hertato, Roni; Azizi, Bagus Salam (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2025)
Financial statement fraud is a highly risky practice in financial reporting. This research aims at investigating the effect of the fraud diamond (Pressure, Opportunity, Rationalization, and Capability) on the probability of financial statement fraud. The sample consisted of 132 cooperatives over three years (2022–2024). The data analysis technique used logistic regression. The findings showed that pressure was a significant factor driving fraud, arising from various financial obligations that had to be met. Opportunity also influenced the occurrence of financial statement fraud, as a weak internal control system created opportunities for manipulation. Rationalization played a role in enabling fraud, as individuals justified their actions through various rationalizations. Additionally, capability increased the potential for fraud, as individuals with specialized knowledge and skills were more likely to commit fraudulent activities. These findings emphasize the importance of strengthening internal controls and addressing financial pressures to mitigate the risk of financial statement fraud.